A pioneering study on training attacking corners in women's football - Libreau, C.; Benguigui, N. (Journal of Physical Education and Sport, 2024)
The objective of this study was to develop a novel approach in women's football aimed at enhancing performance in attacking corners. Drawing upon prior research by Beare & Stone (2019) and Libreau & Benguigui (2024), which highlighted the effectiveness of inswing deliveries aimed at the near post or penalty spot, we conducted a 10-week training program with the Montpellier Hérault Sport Club women's team for 10 weeks at a rate of 2 sessions per week on attacking corners during the second part of the 2021/2022 season, comprising 2 sessions per week dedicated to attacking corners. Following this training protocol, their performances significantly improved in the baseline situation worked on in training. Indeed, the players have improved their danger score by successfully moving more often and with better timing into the ball's arriving zone. They have also shot towards the goal more often and scored more frequently. They also significantly improved their performances in attacking corners in matches. The corner kickers improved their accuracy on shots by sending significantly more balls into dangerous areas (at the near post and at penalty spot). In addition, there were fewer corners that were directly intercepted by the opposing goalkeeper or cleared by the opposing defense. There was also a significant increase in the number of shots taken and the number of goals scored. These results show that specific, regular, and consistent training protocols for attacking corners can improve a team's collective effectiveness in a clearly identified phase of the game, both in training and in the match.